(3TQM ThGgO GdbWQs - (3MSjf (B((3Hf CHj HcQ(B) (3Hf ZfGe GdfLOj GdCMSGFjs; (3GHf gTGe , YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa, LeGd GdOjf , CHh eMeO,J (B761 (3g` s ((3GHf GdedG adGM GdeMehOj GdaVhdj GdHUQj s)
(3ChdgG (B:s
(3hHYO, agPG eG OYJ UZGQ GdWdGH GdfGTFjf aj UfYI GdEYQGH ef JQcjH dThGgO GdbWQ ddYdGeI GHf gTGe s
(3BNQgG (B:s
(3hgj dZI QHjYI hZjQge ef GdYQH jba Ydi GdefUhH HGdCda fMh(B: (3QCjJ RGjOG, hGddg CYde HGdUhGH fLRJ gPG GdcJGH GHf ZfGe QMeg Gddg s
(3HChdgG Jedc aj GdHUQI SfI (B1370(3g`s
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B147 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B163 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B465s
Keywords: (3GdfMhs